Лихоліття Першої світової війни як чинник формування досвіду протистояння викликам воєнного часу в монахів Студійського уставу - Скіра, Ю. Р.; Skira, Yuriy (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглянуто вплив лихоліть Першої світової війни на формування досвіду протистояння викликам воєнного часу в монахів Студійського уставу греко-католицької церкви. Проаналізовано долю цього покоління студитів, представники якого під час Голокосту рятуватимуть євреїв, опираючись на пережитий ними досвід глобальної війни.This article analyses an impact of the hard times of the First World War on the formation of experience in confronting wartime challenges by the monks of the Studite Rite of the Ukrainian Greek Catholic Church. The author shows that the activities of the religious communities of the Ukrainian Greek Catholic Church during the First World War, their lifestyle and perception of events, in the middle of which they found themselves caused by frontline displacement of the two combating blocks, remain underexplored in the Ukrainian history. In most cases, historians study general perception of those challenges by the clergy of the Ukrainian Greek Catholic Church or by a specific church figure. However, a more specific aspect, which concerns the religious, is practically absent in the Ukrainian scientists’ publications. The aim of this article is to highlight the history of the monks community of the Studite Rite from the perspective of acquisition of historical experience in wartime challenges confrontation. The author defends an opinion that this experience was extremely important from the point of view of the future of this community.
Hard Times of the First World War as a Factor of Formation of Experience in Confronting Wartime Challenges by the Monks of the Studite Rite
Keywords: Перша світова війна; монахи; досвід; переслідування; євреї; Голокост; First world war; monks; experience; persecution; Jews; the Holocaust